Global Measurements of Brown Carbon and Estimated Direct Radiative Effects. Issue 13 (1st July 2020) - Zeng, Linghan; Zhang, Aoxing; Wang, Yuhang; Wagner, Nicholas L.; Katich, Joseph M.; Schwarz, Joshua P.; Schill, Gregory P.; Brock, Charles; Froyd, Karl D.; Murphy, Daniel M.; Williamson, Christina J.; Kupc, Agnieszka; et al.
Abstract: Brown carbon (BrC) is an organic aerosol material that preferentially absorbs light of shorter wavelengths. Global‐scale radiative impacts of BrC have been difficult to assess due to the lack of BrC observational data. To address this, aerosol filters were continuously collected with near pole‐to‐pole latitudinal coverage over the Pacific and Atlantic basins in three seasons as part of the Atmospheric Tomography Mission. BrC chromophores in filter extracts were measured. We find that globally, BrC was highly spatially heterogeneous, mostly detected in air masses that had been transported from regions of extensive biomass burning. We calculate the average direct radiative effect due to BrC absorption accounted for approximately 7% to 48% of the top of the atmosphere clear‐sky instantaneous forcing by all absorbing carbonaceous aerosols in the remote atmosphere, indicating that BrC from biomass burning is an important component of the global radiative balance. Plain Language Summary: Combustion produces light‐absorbing aerosols that can affect the global radiation balance. Black carbon, which absorbs light over a broad wavelength range, has been extensively studied, but recent work shows that a significant component of the light‐absorbing aerosol is brown, absorbing mostly in the lower end of the visible and into the ultraviolet (UV). Incomplete combustion, such as in wild fires, is known to produce substantial levels of brown carbon. Here we report direct measurements of brown carbon determined from filter samples collected from aircraft flights that extended from pole to pole over three seasons. We observed brown carbon in aerosols that had been transported long distances from regions of wild fires at various locations across the globe. A radiative transfer model indicated that this brown carbon can substantially contribute to the overall radiative forcing by light‐absorbing aerosols. Key Points: Globally, biomass burning is a large source of light‐absorbing carbonaceous aerosol that directly affect the planetary radiation balance Transported over long distances, brown carbon is a significant component of these aerosols, but its contribution was highly variable Brown carbon contributed up to 48% of average clear‐sky instantaneous forcing by light absorption by carbonaceous aerosols